2005
DOI: 10.2140/agt.2005.5.31
|View full text |Cite
|
Sign up to set email alerts
|

On Davis–Januszkiewicz homotopy types I; formality and rationalisation

Abstract: For an arbitrary simplicial complex K , Davis and Januszkiewicz have defined a family of homotopy equivalent CW-complexes whose integral cohomology rings are isomorphic to the Stanley-Reisner algebra of K . Subsequently, Buchstaber and Panov gave an alternative construction (here called c(K)), which they showed to be homotopy equivalent to Davis and Januszkiewicz's examples. It is therefore natural to investigate the extent to which the homotopy type of a space is determined by having such a cohomology ring. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 21 publications
2
64
0
1
Order By: Relevance
“…A crucial ingredient is provided by the fibration Z K → DJ (K) → BT n , where DJ (K) is the Davis-Januszkiewicz space associated to K. The formality of this space-a result of Franz [22] for smooth toric fans, and Notbohm and Ray [43] in general-leads to the collapse of the Eilenberg-Moore spectral sequence for the path-fibration of DJ (K), thereby allowing us to compute π * (Z K ) ⊗ k in terms of Tor S/I (k, k), the dual of the Yoneda algebra of S/I. The answer turns out to be particularly nice when K is a flag complex, in which case S/I is a Koszul algebra.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial ingredient is provided by the fibration Z K → DJ (K) → BT n , where DJ (K) is the Davis-Januszkiewicz space associated to K. The formality of this space-a result of Franz [22] for smooth toric fans, and Notbohm and Ray [43] in general-leads to the collapse of the Eilenberg-Moore spectral sequence for the path-fibration of DJ (K), thereby allowing us to compute π * (Z K ) ⊗ k in terms of Tor S/I (k, k), the dual of the Yoneda algebra of S/I. The answer turns out to be particularly nice when K is a flag complex, in which case S/I is a Koszul algebra.…”
Section: 2mentioning
confidence: 99%
“…In other words, Z K (X, A) is the colimit of the diagram of spaces {(X, A) σ }, indexed by the category whose objects are the simplices of K (including the empty simplex), and whose morphisms are the inclusions between those simplices; see [46,43].…”
Section: Cellular Cochains and Massey Productsmentioning
confidence: 99%
“…Observe that the homomorphisms i ST * and i * ST are twins in the sense of Notbohm and Ray [16], that is i QT * i ST * = i RQ * i RS * and i ST * i QT * = i RS * i RQ * . The face ring of T and the face rings of Q and S are related as follows:…”
Section: Proposition 45 a Toric Complex T Is Simplicial If And Onlymentioning
confidence: 99%
“…In [7] Davis and Januszkiewicz showed that every StanleyReisner algebra R(K) is realized topologically by a space DJ(K). Subsequent work of Buchstaber and Panov ([3]) has shown the existence of a homotopy equivalent model for DJ(K) as a cellular subcomplex of BT m = (CP ∞ ) m , and Notbohm and Ray ( [13]) expressed it as a homotopy colimit of a certain diagram over the poset category of K.…”
Section: Introductionmentioning
confidence: 99%